Steroid Therapy on Cholestasis: A Case Report - Rendi Aji Prihaningtyas; Bagus Setyoboedi; Sjamsul Arief; Prihaningtyas, Rendi Aji (PT Dexa Medica, 2025)
Introduction: Cholestasis is a pathological condition associated with immune-mediated processes that interfere with bile flow, thus requiring early diagnosis and prompt treatment to ensure optimal outcomes. The use of steroid therapy in the treatment of cholestasis has not been previously reported. Case: A 2-month and 9-day-old male infant presented with jaundice beginning at one week of age, followed by pale stools and tea-colored urine. Physical examination revealed jaundice, hepatomegaly, and splenomegaly. Laboratory investigations showed elevated liver enzymes: aspartate aminotransferase (AST) 292 U/l, alanine transaminase (ALT) 187 U/l, gamma-glutamyl transferase (GGT) 312.7 U/l, and alkaline phosphatase (ALP) 882 U/l), along with elevated bilirubin level (total bilirubin 7.9 mg/dl and direct bilirubin 6 mg/dl). Cytomegalovirus (CMV) IgG was reactive. A two-phase abdominal ultrasound examination revealed a preprandial gallbladder size of 0.65 x 0.33 x 1.91 cm, a postprandial size of 0.37 x 0.29 x 0.73 cm. Liver biopsy revealed chronic hepatitis and mild fibrosis (F1). The patient was treated with methylprednisolone, which was gradually tapered off. Following steroid therapy, liver enzyme and bilirubin levels normalized, gallbladder size increased, and stool color darkened. Posttreatment gallbladder size showed an increase (preprandial 3.05 x 0.96 x 0.72 cm, postprandial 2.45 x 0.72 x 0.82 cm). Conclusions: Steroids may improve bile flow and prevent further liver damage. Targeting immune mechanisms could represent a promising approach for future cholestasis treatments.